The value of the body after death: new possibilities, new conflicts - De Gregorio, Eugenio (Medicina Historica, 2022)
Recently, new and unedited questions connected to the development of technology and digital are facing the reflection on the value of the memory and data of the deceased.The development of modern technologies and digital communication systems requires new reflections on the social and cultural significance of death and on the influence of digital culture in the ways of dealing with the issue of death.The interactivity between users in flesh and blood does not take into account that they can die at any moment, but the presence of the person remains present within the network through actions (their own and others), through speeches and narratives produced and reproduced through various web channels.This makes it very complicated to understand the role and meaning that the data recorded on the web assume post mortem, generating emotional, psychological, social and legal consequences that are still not very clear today and which include the themes of the elaboration of mourning, of personal inheritances and, also, of the transformations of funeral rites.